Sosialisasi Inovasi Produk Hutan Berkelanjutan: Meningkatkan Nilai Tambah Sumber Daya Alam bagi Mahasiswa Kehutanan - Siti Nurhidayati; Khaeruman Khaeruman; Masiah Masiah; Laras Firdaus (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The utilization of non-timber forest products (NTFPs) is still not optimal, despite having great potential in supporting environmental sustainability and the local economy. The need for innovation in forest product management is becoming increasingly urgent, especially in the context of green economic development and natural resource conservation. This activity aims to provide understanding to forestry students of Mandalika University of Education regarding the importance of sustainable forest product innovation, fostering environmental awareness, and instilling character values such as ecological responsibility. This activity involved 30 participants and was carried out in four training sessions that included interactive lectures, group discussions, and individual reflections. The evaluation results showed an increase in participants' conceptual understanding by 42% based on the results of the pre-test and post-test. In addition, participants produced more than 6 creative ideas based on local potential, such as the development of herbal products, environmentally friendly products and natural dyes. Character values such as innovation, ecological responsibility, and environmental awareness were also successfully internalized in the learning process. This socialization makes an important contribution in shaping sustainability awareness and professional readiness of forestry students. It is recommended that this program be continued in the form of applied training that includes the development of NTFP product prototypes and integrated into the green entrepreneurship curriculum.